The Association Between Pregnancy-Related Factors and Health Status Before and After Childbirth With Satisfaction With Skilled Delivery in Multiple Dimensions Among Postpartum Mothers in the Akatsi South District, Ghana - Lawrence Sena Tuglo; Lawrence Sena Tuglo; Lawrence Sena Tuglo; Comfort Agbadja; Cynthia Sekyere Bruku; Cynthia Sekyere Bruku; Vivian Kumordzi; Vivian Kumordzi; Jessica Dzigbordi Tuglo; Jessica Dzigbordi Tuglo; Leticia Atiah Asaaba; Leticia Atiah Asaaba; et al. (Frontiers Media S.A., 2022)
BackgroundSkilled delivery has been a pronounced concern and has been investigated over the years in developing countries. An inclusive understanding of the satisfaction of postpartum mothers is vital in improving the quality of skilled delivery, which is beneath the standard in some parts of developing countries. This study assessed the association between pregnancy-related factors and health status before and after childbirth with satisfaction with skilled delivery in multiple dimensions among postpartum mothers in the Akatsi South District, Ghana.MethodsA community-based, cross-sectional study was conducted among 538 postpartum mothers who participated through the systematic sampling method. Data collection was performed through a pretested and structured questionnaire developed from the WHO responsiveness concept and other prior studies. Questions on satisfaction were categorized into six dimensions. The associations were determined using bivariable and multivariable logistic regression analyses.ResultsThe overall satisfaction of postpartum mothers with skilled delivery was 80.7%. The highest (89.6%) and the lowest (12.8%) satisfaction with skilled delivery were found in technical quality and financial dimensions. Analysis revealed that autonomously age and delivery procedure were significantly associated with the dimensions of communication and responsiveness. Postpartum mothers who delivered at private healthcare facilities [crude odds ratio (COR) = 1.70; (95% CI 1.00-2.90); p = 0.049] had preterm pregnancy before delivery [COR = 2.08; (95% CI 1.02-4.21); p = 0.043], had cesarean section [COR = 2.73; (95% CI 1.05-7.12); p = 0.040], and presented with complications after childbirth [COR = 2.63; (95% CI 1.09-6.35); p = 0.032] were more likely to be satisfied in the dimension of communication only compared to their counterparts. Regarding responsiveness, multiparous mothers [COR = 1.63; (95% CI 1.06-2.51); p = 0.007] were more likely to be satisfied than primiparous mothers. Overall satisfaction was significantly and positively correlated with the various dimensions of skilled delivery.ConclusionsThe majority were satisfied with five dimensions of satisfaction with skilled delivery except for the financial dimension. The District Health Directorate of Akatsi South should take into consideration these findings in their policy development for forward-looking skilled delivery.